Connectivity-based Meta-Bands: A new approach for automatic frequency band identification in connectivity analyses - Rodríguez-González, Víctor; Núñez, Pablo; Gómez, Carlos; Shigihara, Yoshihito; Hoshi, Hideyuki; Tola-Arribas, Miguel Ángel; Cano, Mónica; Guerrero, Ángel; García-Azorín, David; Hornero, Roberto; Poza, Jesús (NeuroImage (Orlando, Fla.), 2023)
The majority of electroencephalographic (EEG) and magnetoencephalographic (MEG) studies filter and analyse neural signals in specific frequency ranges, known as “canonical” frequency bands. However, this segmentation, is not exempt from limitations, mainly due to the lack of adaptation to the neural idiosyncrasies of each individual. In this study, we introduce a new data-driven method to automatically identify frequency ranges based on the topological similarity of the frequency-dependent functional neural network. The resting-state neural activity of 195 cognitively healthy subjects from three different databases (MEG: 123 subjects; EEG1: 27 subjects; EEG2: 45 subjects) was analysed. In a first step, MEG and EEG signals were filtered with a narrow-band filter bank (1 Hz bandwidth) from 1 to 70 Hz with a 0.5 Hz step. Next, the connectivity in each of these filtered signals was estimated using the orthogonalized version of the amplitude envelope correlation to obtain the frequency-dependent functional neural network. Finally, a community detection algorithm was used to identify communities in the frequency domain showing a similar network topology. We have called this approach the “Connectivity-based Meta-Bands” (CMB) algorithm. Additionally, two types of synthetic signals were used to configure the hyper-parameters of the CMB algorithm. We observed that the classical approaches to band segmentation are partially aligned with the underlying network topologies at group level for the MEG signals, but they are missing individual idiosyncrasies that may be biasing previous studies, as revealed by our methodology. On the other hand, the sensitivity of EEG signals to reflect this underlying frequency-dependent network structure is limited, revealing a simpler frequency parcellation, not aligned with that defined by the “canonical” frequency bands. To the best of our knowledge, this is the first study that proposes an unsupervised band segmentation method based on the topological similarity of functional neural network across frequencies. This methodology fully accounts for subject-specific patterns, providing more robust and personalized analyses, and paving the way for new studies focused on exploring the frequency-dependent structure of brain connectivity. •Canonical frequency bands disregard relevant subject-specific neural idiosyncrasies.•A novel frequency band segmentation approach is proposed, the CMB algorithm.•The CMB algorithm is based on the frequency-dependent topology of the functional connectivity.•The CMB algorithm provides an automatic user-specific band segmentation.•The CMB algorithm opens the way for novel, personalized, data-driven connectivity analyses.